Investigating the Short-Term and Long-Term Effects of Electricity Consumption on Economic Growth in Iranian Provinces (An Analysis of PMG-FMOLS Models and VECM Causality) - Mohammad Sharif Karimi; maryam heidarian (مدلسازی اقتصادسنجی, 2017)
Electricity energy as a production factor due to natural and clean efficiency, plays effective role in the sustainable growth and development each country. This study investigates the effect of electricity consumption on economic growth in provinces of the country and during the period 2004-2016. To achieve this goal is used of panel cointegration analysis and Fully Modified Ordinary Least Squares (FMOLS), Dynamic Least Squares (DOLS) and Pooled Mean Group (PMG) and Mean Group (MG) are used to estimate long-term coefficients and to determine the short and long term causality relationship, are used Panel Vector Error Correction Model (VECM). The empirical results indicate a significant effect of electricity consumption on economic growth in provinces of the country in all estimated models. Also, in models have been used the variables of labor force, investment, urbanization rate and literacy rate and their results indicate that there are positive and significant effects on economic growth. Also results of panel causality test shows that there is a bilateral relationship and long-term of electricity consumption to economic growth and vice versa. In addition, patterns results without regard to the Tehran indicate that this has dominant role in increasing electricity consumption.